Answer: y = - 3x + 6
Explanation:
The equation of a straight line can be represented in the slope-intercept form, y = mx + c
Where c = intercept
Slope, m = change in value of y on the vertical axis / change in value of x on the horizontal axis
change in the value of y = y2 - y1
Change in value of x = x2 -x1
y2 = final value of y
y 1 = initial value of y
x2 = final value of x
x1 = initial value of x
Looking at the graph,
y2 = - 3
y1 = 6
x2 = 3
x1 = 0
Slope,m = (- 3 - 6)/(3 - 0) = - 9/3 = - 3
To determine the intercept, we would substitute x = 3, y = - 3 and
m = - 3 into y = mx + c. It becomes
- 3 = - 3 × 3 + c
- 3 = - 9 + c
c = - 3 + 9
c = 6
The equation becomes
y = - 3x + 6